TOWARDS AN INTEGRATIVE MODEL OF THE COUNTRY IMAGE (Marketing Journal, 2026)
This paper introduces an integrative framework for analyzing country image, building on the model proposed by Buhmann and Ingenhoff (2015) and incorporating insights from business studies, political science, and communication research. To connect these dis ciplinary perspectives, the study adopts a communication management approach, which establishes a coherent terminological structure for key concepts such as country image, country reputation, country brand, and country identity. Drawing on this foundation, the author formulates a four -dimensional (4D) model of country image by synthesizing established theories of national identity, attitude formation, and reputation management. The proposed model is designed for comparative research and can be applied acros s different audience groups (e.g., domestic versus international publics) as well as across multiple societal levels, ranging from individual perceptions to mass -mediated prestige and public discourse
Keywords: image; country image; national identity; reputation management; regional competitiveness; Uzbekistan